Forming inter-institutional partnerships to offer pre-registration IPE: a focus group study. Issue 3 (3rd May 2020) - McKinlay, Eileen; Brown, Melanie; Beckingsale, Louise; Burrow, Marla; Coleman, Karen; Darlow, Ben; Donovan, Sarah; Gorte, Tom; Hilder, Jo; Neser, Hazel; Perry, Meredith; Sutherland, Dougal; et al.
ABSTRACT: Interprofessional education (IPE) programs for pre-registration health science students are largely offered within one institution including different schools or faculties. Sometimes in small or regional institutions where there are limited student numbers or few professional training programs, or where larger institutions do not offer particular professional programs, it may be necessary to partner with other institutions to offer IPE. This study sought to explore teacher perspectives of forming inter-institutional partnerships to deliver IPE, in particular, to identify the elements that influence the formation of partnerships. An interpretive descriptive approach was used to thematically analyze data from three focus groups with teachers ( n = 21) working in three different partnerships to deliver IPE to students in Wellington, New Zealand. Two main themes were identified which enabled the development of a model of partnership, with a continuum of complexity depending on whether institutions were on the same page and whether the partnership formed to join an existing IPE program or to create a new IPE program. Forming inter-institution partnerships is a pragmatic solution to providing IPE with benefits to all taking part. Our work showed that time, effort, working with complexity, and ability to stay on the same page are necessary elements for building successful partnerships and all need to be taken into account when planning inter-institution partnerships.